Political Islam in Southeast Asia: Moderates, Radicals and Terrorists by Angel M. Rabasa (London: Oxford University for the International Institute for Strategic Studies, 2003. 82 pages.) (American Journal of Islam and Society, 2004)
The author of this brief study on the political aspects of Southeast AsianIslam is a former State and Defense Department official who originally specializedin Latin American affairs before turning his attention to SoutheastAsia. Rabasa now works for the RAND Corporation, a think tank withclose links to the American national security community.The publisher’s target audience is security policy makers. Therefore,the studies it commissions are part analysis and part policy recommendations,whereby the former is often reduced to the bare essentials. It must besaid that, in this case, Rabasa has succeeded in presenting a reasonably balancedpicture in the space of a mere 80 pages. Already in his introductionthe author observes that, apart from a sharpening divide between militantIslam and the West, the antagonism between radicals and moderates withinthe Muslim world has increased as well, and that strengthening moderateand tolerant tendencies within Islam should be supported.Rabasa sees both external and internal influences contributing to therise of Islamic radicalism. In response to the intrusion of western culture, aheightened sense of Muslim self-awareness has found expression in identity-driven politics. A further polarizing element in Southeast Asian Islam isthe Arabization process carried out by Wahhabi-inspired movements andwith financial support from the Middle East. Other auxiliary factors to theformation of transnational networks connecting Muslim radicals are theIranian revolution, the Afghan war, disillusion over the lack of progress insolving the Palestinian issue, and the eruption of ethnic conflicts involvingMuslims in such areas as Bosnia, Chechnya, and Kashmir.Shifting to internal factors, Rabasa identifies different sets of causesfor each Muslim country and Muslim-dominated region in SoutheastAsia. In the case of Indonesia, the vacuum left by an imploding statestructure following Suharto's fall led to a sharpened political competitionin which some saw Islam as a suitable vehicle to power. Malaysia witnessedincreased rivalry between the ruling UMNO coalition and the Pan-Malay Islamic Party (PAS) for the vote of rural Malays, while in theMuslim-dominated southern regions of Thailand and the Philippines ...